INFLUENCE OF SOCIAL MEDIA ADVERTISEMENT ON THE PATRONAGE OF KITCHEN WARES AMONG FEMALE CIVIL SERVANTS IN KWARA STATE, NIGERIA - SULEMAN, Abubakar Sidiq; ADETUNJI, Aminat Abiodun (Fakultas Pertanian, 2025)
This study investigates the influence of social media advertisement on the patronage of kitchen wares among female civil servants in Kwara State, Nigeria. The study is anchored on uses and gratification theory and adopted survey research methods. Multi-stage sampling techniques were used to select the sample size of 504 participants for the study. A self-administered questionnaire was used as the data collection instrument. Findings from this study revealed that young female civil servants are more exposed to advertisements of kitchen wares on social media because social media are new technologies and younger generations are internet savvy and explorative. This study also found that a high level of exposure influences the purchase behaviour of kitchen wares among female civil servants in Kwara State, Nigeria. The study recommended that advertisers should devise strategies to pull elderly female civil servants to social media so that advertised kitchenware products on social media could record high exposure among this group of prospects